Characterizing in vivo loss of virulence of an HN878 Mycobacterium tuberculosis isolate from a genetic duplication event. (December 2022) - Berube, Bryan J.; Larsen, Sasha E.; McNeil, Matthew B.; Reese, Valerie A.; Pecor, Tiffany; Kaur, Suhavi; Parish, Tanya; Baldwin, Susan L.; Coler, Rhea N.
Abstract: The increase of global cases of drug resistant (DR) Mycobacterium tuberculosis (M.tb) is a serious problem for the tuberculosis research community and the goals to END TB by 2030. Due to the need for advancing and screening next generation therapeutics and vaccines, we aimed to design preclinical DR models of Beijing lineage M.tb HN878 strain in different mouse backgrounds. We found escalating sensitivities of morbidity due to low dose aerosol challenge (50–100 bacilli) in CB6F1, C57BL/6 and SWR mice, respectively. We also observed that pulmonary bacterial burden at morbidity endpoints correlated inversely with survival over time between mouse strains. Interestingly, with in vitro passaging and in the process of selecting individual DR mutant colonies, we observed a significant decrease in in vivo HN878 strain virulence, which correlated with the acquisition of a large genetic duplication. We confirmed that low passage infection stocks with no or low prevalence of the duplication, including stocks directly acquired from the BEI resources biorepository, retained virulence, measured by morbidity over time. These data help confirm previous reports and emphasize the importance of monitoring virulence and stock fidelity.